2008
DOI: 10.1016/j.compstruct.2008.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Core crush criterion to determine the strength of sandwich composite structures subjected to compression after impact

Abstract: In this study a core crush criterion is proposed to determine the residual strength of impacted sandwich structures. The core of the sandwich is made of a Nomex Honeycomb core and the faces are laminated and remain thin. The mechanism of failure of this kind of structure under post-impact compressive loading is due to interaction between three mechanical behaviors: geometrical nonlinearity due to the skin's neutral line offset in the dent area, nonlinear response of the core and damages to the skins. For the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…These tests have demonstrated that asymmetrical sandwich structures have exceptional compressive and impact behavior. In particular, the boundary conditions of these structural tests are very different from those of conventional Compression After Impact (CAI) tests [37] and are very conservative because, once the damage has initiated, it quickly propagates to the free edges. Tests at this level have the characteristic of being less conservative and more representative than the normalized uniaxial tests.…”
Section: State Of the Art And Positioningmentioning
confidence: 99%
“…These tests have demonstrated that asymmetrical sandwich structures have exceptional compressive and impact behavior. In particular, the boundary conditions of these structural tests are very different from those of conventional Compression After Impact (CAI) tests [37] and are very conservative because, once the damage has initiated, it quickly propagates to the free edges. Tests at this level have the characteristic of being less conservative and more representative than the normalized uniaxial tests.…”
Section: State Of the Art And Positioningmentioning
confidence: 99%
“…Stiff and simultaneous light component is very important in nowadays industries. To achieve lightweight and high stiffness component, sandwich structure construction is develop [1][2][3][4].…”
Section: Sandwich Structurementioning
confidence: 99%
“…The advantages of sandwich structures include great stiffness to weight ratios [2][3][4][5] , improved fatigue life, steadiness under compressive forces, good thermal and acoustic isolation properties. These benefits determine the fact that the use of composites has improved ominously in a wide range of structural applications and first of all in aerospace manufacturing [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the related literature, the main topic is clearly the compressive response, a phenomenon that has been studied for a long time (see McFarland since 1965 [12] or Wierzbicki [13]). Many authors have studied the compressive behavior -mainly to analyse the energy absorbing capabilities of honeycomb ( [12][13][14][15][16][17] for example) or, more precisely, the crush behavior of the core after a low-velocity/low-energy impact on a sandwich [17][18][19][20][21][22][23][24]. Today, the tendency is to use very refined finite element analysis with explicit code to model the complex failure mode following crushing of the Nomex Honeycomb core.…”
Section: Introductionmentioning
confidence: 99%
“…However, by understanding the structural behavior of the hexagonal cell and by making an analogy with the postbuckling of stiffened structures [22], it is possible to propose simplified discrete models that are very accurate [22][23][24].…”
Section: Introductionmentioning
confidence: 99%